2007
DOI: 10.1038/sj.mp.4001997
|View full text |Cite
|
Sign up to set email alerts
|

TGFB-induced factor (TGIF): a candidate gene for psychosis on chromosome 18p

Abstract: Schizophrenia (SC) and bipolar disorder (BP) share many clinical features, among them psychosis. We previously identified a putative gene locus for psychosis on chromosome 18p in a sample from the Central Valley of Costa Rica (CVCR) population. The present study replicated the association to a specific allele of microsatellite marker D18S63 on 18p11.3, using a newly collected sample from the CVCR. A combined analysis of both samples, plus additional subjects, showed that this specific allele on D18S63, which l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 54 publications
(60 reference statements)
0
7
0
1
Order By: Relevance
“…Despite the fact that several studies have identified potential loci [Bassett, 1992; McInnes et al, 1996; Escamilla et al, 2001; Mukherjee et al, 2006] and candidate genes (TGIF [Chavarría‐Siles et al, 2007], NDUFV2 [Wasizuka et al, 2009], VAPA [Lohoff et al, 2008], NAPG [Weller et al, 2006], IMPA2 [Yoshikawa et al, 2001; Sjøholt et al, 2004], GNAL [Tsiouris et al, 1996]) related to schizophrenia and bipolar disorder as being on chromosome 18p, the three 18p‐ subjects here showed no evidence of psychotic or affective pathology. Nevertheless, given the small sample size of 18p‐ subjects here, we recommend screening for psychosis and bipolar disorder, in addition to ADHD and anxiety disorders, given the above mentioned reports of linkage for these disorders to chromosome 18p and at least one previous report of psychosis in a subject with an 18p‐ deletion [Babovic‐Vuksanovic et al, 2004].…”
Section: P Deletion Subjects and Their Syndromesmentioning
confidence: 99%
“…Despite the fact that several studies have identified potential loci [Bassett, 1992; McInnes et al, 1996; Escamilla et al, 2001; Mukherjee et al, 2006] and candidate genes (TGIF [Chavarría‐Siles et al, 2007], NDUFV2 [Wasizuka et al, 2009], VAPA [Lohoff et al, 2008], NAPG [Weller et al, 2006], IMPA2 [Yoshikawa et al, 2001; Sjøholt et al, 2004], GNAL [Tsiouris et al, 1996]) related to schizophrenia and bipolar disorder as being on chromosome 18p, the three 18p‐ subjects here showed no evidence of psychotic or affective pathology. Nevertheless, given the small sample size of 18p‐ subjects here, we recommend screening for psychosis and bipolar disorder, in addition to ADHD and anxiety disorders, given the above mentioned reports of linkage for these disorders to chromosome 18p and at least one previous report of psychosis in a subject with an 18p‐ deletion [Babovic‐Vuksanovic et al, 2004].…”
Section: P Deletion Subjects and Their Syndromesmentioning
confidence: 99%
“…Por último, ha existido una relación consistente entre el cromosoma 18 y trastornos psiquiátricos en la población costarricense. Para esquizofrenia, la señal de ligamiento inicial en el brazo corto de ese cromosoma fue reportada por (Walss-Bass et al, 2005) y posteriormente replicada en una muestra independiente de Costa Rica por (Chavarría-Siles et al, 2007). La misma región había sido previamente encontrada en pacientes con una forma severa de trastorno bipolar tipo I .…”
Section: Esquizofreniaunclassified
“…Notably, large numbers of cytokines/growth factors and hormones involved in systemic conditions also have distinct neural functions, some currently emerging as potential contributors to the pathophysiology of neurological and psychiatric disorders. For instance, interleukin 1 and 6, tumor necrosis factor α, transforming growth factor β1 and brain derived growth factor have been consistently found to be altered in psychiatric illnesses such as mood disorders and schizophrenia, and suggested to mediate interactions between these illnesses, inflammation and stress (Barbosa et al, 2014; Catena-Dell’Osso et al, 2013; Chavarria-Siles et al, 2007; Fineberg and Ellman, 2013; Hashimoto, 2010; Kim et al, 2004; Poon et al, 2013; Rosenblat et al, 2014). Several of these cytokines were shown directly affect GABAergic transmission, impacting GABA A-mediated synaptic strength and dendritic homeostasis (Beattie et al, 2002; Benes, 2010; Stellwagen et al, 2005; Sun et al, 2010; Vezzani et al, 2008; Wang et al, 2000), pointing to the need to better understand, as well as control for, the relationships between immune factors and neurotransmission in psychiatric disorders..(Benes, 2010)…”
Section: Comorbiditymentioning
confidence: 99%